2014
DOI: 10.1002/bit.25197
|View full text |Cite
|
Sign up to set email alerts
|

Factors impeding enzymatic wheat gluten hydrolysis at high solid concentrations

Abstract: Enzymatic wheat gluten hydrolysis at high solid concentrations is advantageous from an environmental and economic point of view. However, increased wheat gluten concentrations result in a concentration effect with a decreased hydrolysis rate at constant enzyme-to-substrate ratios and a decreased maximum attainable degree of hydrolysis (DH%). We here identified the underlying factors causing the concentration effect. Wheat gluten was hydrolyzed at solid concentrations from 4.4% to 70%. The decreased hydrolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…approximately 30% starch) did not induce any mass transfer limitations. This is in line with a previous study, where no mass transfer limitations were observed in high-solid VWG hydrolysis up to 50% solids (Hardt et al, 2014). Similar observations were done in a high-solid cellulose hydrolysis, where it was shown that the addition of 15% (w/w) water-insoluble, non-hydrolyzable dextrans had no effect on the hydrolysis of 5% cellulose slurries (Selig et al, 2012), which is comparable to water-insoluble, nonhydrolyzable starch in gluten hydrolysis.…”
Section: Influence Of the Solid Contentsupporting
confidence: 92%
See 3 more Smart Citations
“…approximately 30% starch) did not induce any mass transfer limitations. This is in line with a previous study, where no mass transfer limitations were observed in high-solid VWG hydrolysis up to 50% solids (Hardt et al, 2014). Similar observations were done in a high-solid cellulose hydrolysis, where it was shown that the addition of 15% (w/w) water-insoluble, non-hydrolyzable dextrans had no effect on the hydrolysis of 5% cellulose slurries (Selig et al, 2012), which is comparable to water-insoluble, nonhydrolyzable starch in gluten hydrolysis.…”
Section: Influence Of the Solid Contentsupporting
confidence: 92%
“…5 is related to a concentration effect present in protein hydrolysis: the DH% decreases for higher protein concentrations and at constant enzymeto-substrate ratio. This concentration effect has been reported for protein concentrations above 10% in wheat gluten hydrolysis (Hardt, Janssen, Boom, & van der Goot, 2014) and above 1% in whey protein hydrolysis (Butr e, Wierenga, & Gruppen, 2012), and is thus also present at relatively low wheat gluten concentrations of 3e10%.…”
Section: Fig 5 Illustrates the Influence Of The Protein Concentratiomentioning
confidence: 81%
See 2 more Smart Citations
“…Another strategy involves the solution pH. Additionally, high solid loading is generally required to increase the ethanol concentration and to reduce water consumption (Hardt et al, 2014;Luterbacher et al, 2012;Modenbach and Nokes, 2012;Zhang et al, 2010). Thus, we developed a pH-trigged adsorption-desorption approach for cellulase recycling (Shang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%